Analisis Kuantitatif Pengaruh Literasi Akuntansi terhadap Perencanaan Dan Pengendalian Keuangan Pribadi Generasi Z: Quantitative Analysis of the Effect of Accounting Literacy on Financial Planning and Control among Generation Z - Nadia septiani; Muhammad Aqila Putra Nugroho; Zahra Rizkya Wanggana; Grace Putri Zega; Nadya Ranjani Nasaf; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Generation Z is a young age group that has begun to manage personal finances independently; however, many individuals still experience difficulties in managing their finances effectively. This condition is generally caused by limited understanding of basic accounting concepts and a lack of awareness in daily financial management. This study aims to examine the influence of basic accounting understanding, financial literacy ability, and personal accounting literacy awareness on financial management behavior among Generation Z.The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 115 respondents classified as Generation Z and were analyzed using multiple linear regression with the assistance of SPSS version 23. The results indicate that both partially and simultaneously, accounting literacy variables have a significant effect on personal financial management behavior. Among these variables, personal accounting literacy awareness was found to be the most dominant factor influencing respondents’ financial behavior. These findings suggest that improving understanding and awareness of accounting literacy can help Generation Z manage their finances in a more planned and responsible manner.